A review of the Mexican Frankliniella paricutinensis species assemblage in the Intonsa group (Insecta, Thysanoptera: Thripidae), with description of a new species Revisión del ensamble específico mexicano Frankliniella paricutinensis en el grupo Intonsa y descripción de una especie nueva (Insecta, Thysanoptera: Thripidae) - Roberto M. Johansen (Revista Mexicana de Biodiversidad, 2009)
A second review of the 13 Mexican species in the Frankliniella paricutinensis Johansen species assemblage is presented, including the description of a new species. It was sampled from the onion Allium cepa L. agro-ecosystem, in 2 different localities in southern Tamaulipas. The study includes new records for 7 of the 13 previously described species. New morphological data, measurements of several specimens, and illustrations of head, thorax and abdomen, together with some ecological comments, are also included for the new species. A new key for the determination of the 14 species in the F. paricutinensis assemblage is provided. Se hace la segunda revisión de las 13 especies mexicanas integrantes del ensamble específico Frankliniella paricutinensis Johansen. También se incluye la descripción de una especie nueva afín a este ensamble específico encontrada en agroecosistemas de cebolla Allium cepa L. en 2 localidades del sur del estado de Tamaulipas. El estudio incluye registros nuevos de 7 de las 13 especies previamente descritas. Se incluyen con la descripción de la especie nueva, datos morfológicos, medidas de varios ejemplares, así como ilustraciones de cabeza, tórax y abdomen, junto con algunos comentarios ecológicos. Se incluye una clave nueva para la determinación de las 14 especies del ensamble F. paricutinensis.